DESIGN AND DEVELOPMENT AN ORAL QUESTIONING (P-LISAN) MODEL: A NEED ANALYSIS - Samijah Ruwiyah; Fatin Aliah Phang; Nor Farahwahidah Abdul Rahman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The current teaching methods in matriculation colleges often lack interactive and engaging approaches, leading to limited student comprehension and participation in physics. The objective of this study is to identify the elements in the oral questioning model of matriculation college Physics teachers. This study aims to explore the needs to design and development needs of an oral questioning model for physics lecturers at matriculation colleges. In this needs analysis phase, the research adopts a qualitative approach, utilizing semi-structured interviews based on themes identified in the study. The interview protocol was developed, validated, and underwent a preliminary study to ensure reliability. Informants were selected through purposive sampling, focusing on individuals with over five years of experience in education, classified as experts. This purposive sampling method ensured that the participants have relevant expertise and experience to provide valuable insights into the requirements for the P-Lisan model. The findings from the interviews revealed a consensus among all participants on the necessity of developing a questioning model. Additionally, the participants identified specific design elements and features that should be incorporated into the model to address the unique challenges faced by physics lecturers in the matriculation context in Malaysia.